Cadenas globales de valor: El caso de Bolivia - Beatriz Muriel Hernández; Alejandro Herrera J. (Institute for Advanced Development Studies (INESAD), 2017)
– This paper analyzes Bolivian Global Value Chains (GVC) for 2002, 2005 and 2011, using the Vertical Specialization Index (EV) of Hummels et al. (2001) and the measure of Upstreamness of Antràs y Chor (2011) (cited by Antràs et al., 2012b). Indicators show that trade patterns are represented by a concentration of raw materials, which have also taken advantage from those derived from GVC; while manufacturing sectors have been less important in this dynamic, and they even lost their relevance over time.
Keywords: C02; F01; F14; 330; Global Value Chains; fragmentation indicators; Bolivia